Comparative study of DRASTIC-LU and radioactive isotope approaches for assessing groundwater vulnerability to pollution: the case study of Abuja, North Central Nigeria - Mary Nsikanabasi Etuk; Priscilla E. S. Lartsey; Raphael Maduka; Chinero Nneka Ayogu; Igwe ogbonnaya (Discover Water)
Abstract Groundwater resources in Abuja, North Central Nigeria, are facing increasing vulnerability to pollution due to urbanization and anthropogenic activity. There are several methods of assessing groundwater vulnerability to contamination. Choosing the appropriate method for the study site, which is paramount for accurate vulnerability assessment, is sometimes very tasking. The DRASTIC-LU and 3H radioactive tracer methods were assessed in this study and applied to the Abuja aquifers. Water scientists have widely adopted these methods in vulnerability assessments. From the final DRASTIC-LU vulnerability map, it was observed that high to very high vulnerability areas were located in southwestern and northeastern parts of the area. 33% of the wells in the entire area exceed the nitrates statutory limits for drinking water, while 87% of the wells exceeding the nitrates statutory limits were located in high to very highly vulnerable areas. The radioactive tracers provided information on an Abuja aquifer-wide basis, showing areas of most recent recharge (post-nuclear) and older recharge (pre-nuclear), respectively. With the tracer approach, areas of preferential flow and diffuse flow indicating high vulnerability and low vulnerability, respectively, were mapped. This systematic review discusses in detail the advantages and limitations of these methods employing the origin-pathway-target model of vulnerability assessments as the basics of the study. Finally, the application of a dual approach involving the combination of the two is best for vulnerability assessments. This study therefore proposes the need for policymakers to adopt combined methodological approaches for sustainable groundwater management.